MENEROPONG TENTANG KEBIJAKAN KRIMINALISASI TERHADAP TERORISME - Harun, Muhamad (Nurani, 2013)
Abstract:  Terrorism has become a part of the extra-ordinary crimes which damage the economic system, the integrity of the country, innocent civilians as well as other public facilities in the context of the law against all significant. Sheltering terrorists as agents of political offenses or political purpose made with purpose of violence in which the action is intended to create a shock or intimidation to governmental authority or resulting to the public by innocent.ملخص: وقد أصبح الإرهاب جزءا من الجرائم غير العادية التي تتلف النظام الاقتصادي، وسلامة البلاد، المدنيين الأبرياء، فضلا عن غيرها من المرافق العامة في إطار القانون ضد كل كبير. إيواء الإرهابيين وكلاء من جرائم سياسية أو غرض سياسي المصنوع من هدف من العنف الذي يقصد العمل لخلق صدمة أو الترهيب للسلطة حكومية أو الناشئين للجمهور بواسطة الأبرياء.Kata kunci: kriminalisasi, terorisme, pemerintah.